2012
DOI: 10.1016/j.bbmt.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Growth Factor and Stem Cell Factor to Improve Thymopoiesis after Autologous CD34+ Cell Transplantation in Rhesus Macaques

Abstract: Deficient thymopoiesis and retarded recovery of naive CD4(+) T cells are important determinants of insufficient immune-competence following hematopoietic stem cell transplantation (HSCT). Although keratinocyte growth factor (KGF) may protect the thymic epithelium, stem cell factor (SCF) is involved in early thymopoiesis. We evaluated whether KGF alone or combined with SCF would affect thymopoiesis and hematologic recovery following myeloablative autologous HSCT into rhesus macaques. Purpose-bred adult rhesus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…As a consequence, efforts to improve thymic reconstitution using cytokines [IL7 (25), SCF, KFG (26,27), FLT3L (28)] or hormones [growth hormone (29), thyroid-stimulating hormone (30), and ablation of sex hormones (31)] are only likely to be effective if they selectively act on the thymic microenvironment or mimic signals given by the thymic epithelial cells to developing thymocytes. Transplantation of committed T-cell progenitors together with HSCT, as shown before with mouse hematopoietic cells cultured ex vivo on OP9-DL1 expressing stromal supportwhich provide the cells with the Notch signals required to direct T-cell development (32)-as well as diminishing the influence of male sex hormones known to deregulate intrathymic Notch ligand DLL4 (31) may work well to improve thymic function and support diverse TCR repertoire formation.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, efforts to improve thymic reconstitution using cytokines [IL7 (25), SCF, KFG (26,27), FLT3L (28)] or hormones [growth hormone (29), thyroid-stimulating hormone (30), and ablation of sex hormones (31)] are only likely to be effective if they selectively act on the thymic microenvironment or mimic signals given by the thymic epithelial cells to developing thymocytes. Transplantation of committed T-cell progenitors together with HSCT, as shown before with mouse hematopoietic cells cultured ex vivo on OP9-DL1 expressing stromal supportwhich provide the cells with the Notch signals required to direct T-cell development (32)-as well as diminishing the influence of male sex hormones known to deregulate intrathymic Notch ligand DLL4 (31) may work well to improve thymic function and support diverse TCR repertoire formation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a non-human primate model showed that adult rhesus macaques, receiving KGF after autologous HSCT, had accelerated hematopoietic recovery, improved thymopoiesis (as evaluated by TREC analysis) and enhanced naïve T cell recovery following transplant. However, the increase in T cell recovery was not associated with an improved immunity against CMV reactivation or an improved response to tetanus toxoid vaccination (129). However, while KGF can also promote the expansion of young and old thymi in mice (68), there is some debate as to its effectiveness in promoting steady-state thymopoiesis in non-human primates (129).…”
Section: Exogenous Strategies To Enhance Thymic Recoverymentioning
confidence: 99%
“…However, the increase in T cell recovery was not associated with an improved immunity against CMV reactivation or an improved response to tetanus toxoid vaccination (129). However, while KGF can also promote the expansion of young and old thymi in mice (68), there is some debate as to its effectiveness in promoting steady-state thymopoiesis in non-human primates (129). …”
Section: Exogenous Strategies To Enhance Thymic Recoverymentioning
confidence: 99%
“…Pharmacological administration of FGF7 or keratinocyte growth factor (KGF) represses the Ink4a tumor-suppressor gene and partially rejuvenates the murine thymocyte progenitors (Berent-Maoz et al 2012). FGF improves thymopoiesis as well as engraftment following myeloablative stem cell transplantation in rhesus macaques (Wils et al 2012). Palifermin is a pharmaceutical form of recombinant human KGF (rhKGF) (Tamari et al 2012), and its administration leads to regeneration of epithelial tissues after injury (Finch et al 2013).…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%